2004 new and renewable energy technologies for sustainable development, Evora, Portugal, 28 June-1 July 2004 - Conference on New and Renewable Energy Technologies for Sustainable Development (2004 : Evora, Portugal); Afgan, Naim; Carvalho, M. G. (Maria da Graca), 1955- (Hackensack, NJ : World Scientific Pub. Co., 2007)
19